2012
DOI: 10.1111/j.1365-2702.2011.04025.x
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a caregiver: new family carers’ experience during the transition from hospital to home

Abstract: The findings of this study can stimulate healthcare professionals to acquire effective communication skills and display an empathic attitude when assessing caregivers' needs in the particularly challenging phase of transition from hospital to home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
142
0
11

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(157 citation statements)
references
References 41 publications
3
142
0
11
Order By: Relevance
“…In contrast, a longitudinal study with 18 caregivers of dependent patients on two occasions of before and after hospital discharge emphasizes that what changed over time was just the focus of the questions. Concerns of the caregivers slowly moved away from the recipient only in the post-discharge period, and they began to seek recognition of their own needs and appreciate the care provided (11) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, a longitudinal study with 18 caregivers of dependent patients on two occasions of before and after hospital discharge emphasizes that what changed over time was just the focus of the questions. Concerns of the caregivers slowly moved away from the recipient only in the post-discharge period, and they began to seek recognition of their own needs and appreciate the care provided (11) .…”
Section: Resultsmentioning
confidence: 99%
“…A longitudinal study of 60 family caregivers for patients of a stroke (cerebrovascular accident -CVA) observed a change in the needs of caregivers over time: before hospital discharge, two weeks after hospitalization and 3 months after hospitalization, revealing a decrease of these needs over time (14) . The omnipresent fear of the unknown enhances the perceived lack of information and preparation, especially in the pre-discharge period, but reducing in the post-discharge period (11) . The same results are presented in another longitudinal study of 10 family caregivers for patients with Motor neuron disease/ Amyotrophic Multiple Sclerosis, followed for 2 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Caregivers of stroke survivors play a pivotal role in assisting in the physical, cognitive and emotional needs of stroke survivors 20 ; however, they often feel unprepared for their new caregiver role. 21,22 These issues can cause increased errors in care, duplication of services, and inappropriate or absent treatment for stroke survivors, and even increased risk for patients' readmission to hospital. 23 Several studies demonstrated that well-prepared caregivers can significantly influence stroke survivors' recovery and quality of life.…”
Section: Introductionmentioning
confidence: 99%